A new alpheid shrimp, Alpheus mannarensis sp. nov. (Crustacea; Decapoda; Alpheidae) from Gulf of Mannar, Southern India - Purushothaman, P.; Abhilash, C.p.; Kumar, T.t. Ajith; Lal, K. K. (Zootaxa, 2021)
A new species of the genus Alpheus Fabricius, 1798, A. mannarensis sp. nov. is described and represented based on the materials collected from the shallow and rocky reefs, Gulf of Mannar (Thoothukudi waters), Southern India. This is the first report of Alpheus species from the Gulf of Mannar region. The new species is assigned to the Alpheus brevirostris group, and is distinguished from other species of this group by the combination of the following features: rostral ridge lower than orbital hood in lateral view and postrostral carina not extended to the middle of the carapace, palm of major chela with a transverse groove near the base of dactylus, the ultimate segment of the third maxilliped slender, fingers of minor chela of male slightly longer than palm, the first carpal segment of second pereiopods shorter than second segment, merus of third pereiopods slender and unarmed, dactylus of third pereiopods slender and subspatulate, and unique colour patterns of longitudinal light lines on the reddish body.